PENGARUH MANAJEMEN LABA, KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Rika Milanda Sari, I Gusti Ayu; Sri Harta Mimba, Ni Luh Putu (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
Corporate Social Responsibility (CSR) is a form of social responsibility and a firm commitment to stakeholders and environments around the company. This study aims to determine the effect of earnings management, financial performance, company size and growth on the company's CSR disclosure in mining sector companies listed in Indonesian Stock Exchange from 2008 till 2012. This study uses secondary data such as annual reports and corporate sustainability report mining sector. The study samples consisted of six mining companies listed in Indonesian Stock Exchange from 2008 till 2012 were obtained from the www.idx.co.id websites and corporate websites. The results show that only company size that has a positive effect on CSR disclosure. Other variables such as earnings management, financial performance, and growth of the company have no significant effect on CSR disclosure.
Keywords: Corporate Social Responsibility; earnings management; financial performance; size; growth.